IMPLEMENTASI KEBIJAKAN PENGELOLAAN PAJAK RUMAH SEWA DI KOTA JAYAPURA - Noak Tabo; Untung Muhdiarta (JURNAL KEBIJAKAN PUBLIK, 2022)
This study aims to analyze and determine the implementation of rental house management policies in Jayapura City, as well as analyze the supporting and inhibiting factors for implementing the policy. This study uses a qualitative descriptive approach conducted in Jayapura City, the determination of informants is carried out by snowball. Data collection techniques used are observation and interviews. Data analysis includes the stages of data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Regional Regulation Number 13 of 2016 concerning Rental Houses in Jayapura City. Judging from the aspect of communication and information dissemination, it has been carried out by utilizing information technology and installing billboards as an appeal to the public to pay taxes, including rental house taxes. In the aspect of resources owned, the quality of the resources is inadequate and does not meet the adequacy aspect, so it is very necessary to hold training and technical guidance as well as increase the level of education to improve aspects of management and service delivery. Disposition is going quite well based on the high commitment that exists at the District office level. Then, the Bureaucratic Structure is based on the authority and responsibility given in governance, but does not yet have an SOP so that the division of tasks and main functions is still unclear. the supporting factor is the institutional aspect that involves all components of the related unit, as well as the commitment of all existing personnel in managing governance and providing services to the community. Then the inhibiting factors are the quality of human resources which are still very lacking and the lack of facilities and infrastructure to support governance in implementing these policies.